Controls for abuse clauses in law 1480 of 2011: a reflection from the economic analysis of the law (2018)
Objective. This article proposes a critical reflection about the abusive clauses in contracts for the adhesion in the relations of consumption and their regulation in Law 1480 of 2011. Methodology. Hermeneuticsynthetic characterization, in which the assumptions of economic analysis of law are used, starting with the definition of abusive clause, analyzing then the criteria established to determine abuse always in the context of consumption. Finally, reference is made to the controls designed for this kind of clauses as a form of intervention to the reality that the market for goods and services demands from public authorities. Results. The freedom and equality of the parties that demand a reliable market shields protection in two legal spheres: patrimonial rights and personal rights as for the worthy consumption. Conclusion. Greater efficiency of administrative control against the use of this type of clauses in consumer relations is needed.